Editorial: Special Issue “From Waste to Energy: Anaerobic Digestion Technologies” - Christian Aragón-Briceño; Panagiotis Boutikos; Musa Manga (Energies)
Anaerobic digestion (AD) has become a cornerstone in the global pursuit of sustainable energy solutions and effective waste management [...]